2015
DOI: 10.2116/analsci.31.573
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex MicroRNA Detection on a Power-free Microfluidic Chip with Laminar Flow-assisted Dendritic Amplification

Abstract: MicroRNA (miRNA) profile-based point-of-care (POC) diagnostic methods have attracted considerable attention. In our laboratory, singleplex miRNA detection on a power-free poly(dimethylsiloxane) (PDMS) microfluidic chip with laminar flow-assisted dendritic amplification (LFDA) has been developed. In this study, to obtain the miRNA profile and to improve the reliability of the diagnosis, multiplex miRNA detection on the same system is demonstrated without compromising any advantages of the singleplex miRNA detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…[17][18][19][20][21] As a preliminary experiment, we had confirmed that B-anti-IgG is as effective as B-anti-SA for induction of LFDA using the well-established miRNA detection system (Fig. S1 in Supporting Information).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…[17][18][19][20][21] As a preliminary experiment, we had confirmed that B-anti-IgG is as effective as B-anti-SA for induction of LFDA using the well-established miRNA detection system (Fig. S1 in Supporting Information).…”
Section: Resultsmentioning
confidence: 69%
“…CP-1 or CP-2 was immobilized onto the glass surface as described elsewhere. 20,21 Briefly, 1% glutaraldehyde in carbonate buffer was reacted with an aminated glass slide (SD00011, Matsunami Glass) at 37 C for 2 h. A PDMS part having a straight microchannel was attached onto the glass surface. CP-1 or CP-2 (100 μM) in ultrapure water was injected into the microchannel and incubated at 37 C for 1 h. The PDMS part was detached from the glass surface in a stopping buffer (25 mM Tris, 0.05% Tween 20), and the glass substrate was washed by ultrasonication in the stopping buffer, followed by deionized water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Our method has two distinct features. First, the microfluidic chip requires no external power source for fluid pumping, because the pumping is achieved by degassed poly(dimethylsiloxane) (PDMS), which is widely employed as a microfluidic chip material.…”
Section: Introductionmentioning
confidence: 99%
“…We have also reported that our method can easily be expanded to the simultaneous triplex detection of miR-16, miR-21, and miR-500. 21 These previous studies were carried out with artificial samples containing only purified target miRNAs. Although the latter paper 21 revealed that our method produced no cross-reaction between those totally different sequences, the detection specificity of our method has been largely unexplored.…”
Section: Introductionmentioning
confidence: 99%